2008
DOI: 10.1152/ajprenal.00131.2008
|View full text |Cite
|
Sign up to set email alerts
|

Antiapoptotic properties of erythropoiesis-stimulating proteins in models of cisplatin-induced acute kidney injury

Abstract: Erythropoietin (Epo) induces erythrocytosis by suppressing erythroid progenitor cell apoptosis through the Janus-activated kinase-signal transducers and activators of transcription (JAK-STAT) pathway. Since apoptosis contributes to cisplatin (CP)-induced nephrotoxicity and Epo receptors (EpoR) are expressed in the kidney, we examined the role of antiapoptosis in recombinant human erythropoietin (rHuEpo)-mediated renal protection. In human renal proximal tubular epithelial (RPTE) cells in culture, rHuEpo, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 36 publications
(44 reference statements)
4
49
0
2
Order By: Relevance
“…Recent studies have demonstrated that EPO and TPCs, nonerythropoietic derivatives of EPO, protect a wide variety of tissues (21)(22)(23)(24), including the heart, from I/R injury (16)(17)(18). These protective effects of EPO and TPCs have been shown in part to be mediated by preventing apoptosis (16)(17)(18)24). Our data are consistent with previous findings observed for EPO and TPCs and confirm the antiapoptotic effect of HBSP on cardiomyocytes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recent studies have demonstrated that EPO and TPCs, nonerythropoietic derivatives of EPO, protect a wide variety of tissues (21)(22)(23)(24), including the heart, from I/R injury (16)(17)(18). These protective effects of EPO and TPCs have been shown in part to be mediated by preventing apoptosis (16)(17)(18)24). Our data are consistent with previous findings observed for EPO and TPCs and confirm the antiapoptotic effect of HBSP on cardiomyocytes.…”
Section: Discussionsupporting
confidence: 92%
“…This effect is comparable with that observed for EPO on a molar basis, and similarly obtained regardless of timing of treatment. Recent studies have demonstrated that EPO and TPCs, nonerythropoietic derivatives of EPO, protect a wide variety of tissues (21)(22)(23)(24), including the heart, from I/R injury (16)(17)(18). These protective effects of EPO and TPCs have been shown in part to be mediated by preventing apoptosis (16)(17)(18)24).…”
Section: Discussionmentioning
confidence: 99%
“…11 Our results showed that administration of EPO significantly decreased the number of apoptotic cells when compared with untreated flaps and animals receiving L-Name only. This is in line with a previous study of our group, in which we could show that apoptotic cell death was significantly reduced even if EPO was administered only after flap elevation.…”
Section: Epo Enos Ischemic Damage and Skin F Rezaeian Et Almentioning
confidence: 51%
“…Recent findings revealed tissue-protective properties of EPO independent of its hematopoietic properties in a variety of organ systems suffering from ischemia, such as the heart, 5 brain, 6,7 liver, 8 kidney 9 and the striated muscle. 10 EPO initiates a multitude of EPO receptor-dependent and -independent cellular pathways, including the induction of anti-apoptotic genes 11 and anti-inflammatory molecules, 12 the increase of vascular endothelial growth factor (VEGF), as well as the production of vasodilative molecules such as nitric oxide (NO). 13 NO is an enzymatic product from L-arginine that mediates numerous biological actions through the activation of cyclic guanosine monophosphate, which inhibits intracellular calcium release and induces smooth muscle relaxation.…”
mentioning
confidence: 99%
“…Recent work has shown that EPO and its nonerythropoietic derivatives, including HBSP, provide tissue-protective effects in a wide variety of tissues, in part by inhibiting apoptosis and by counteracting proinflammatory cytokines such as TNF-α (13,(22)(23)(24)(25)(26). Consistent with these observations, our data obtained from the in vitro experiments clearly demonstrate that HBSP, as well as EPO, reduces HUVEC apoptosis and THP-1 production of TNF-α and MMP-9 induced by CRP, a direct mediator of atherosclerosis (16,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%